2017
DOI: 10.5304/jafscd.2017.072.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Use of Food Storage Structures by Agrarian Communities in Northern Uganda

Abstract: Food storage at the national or global level is important due to its multifunctional roles of enhancing food access, nutrition, and income security at the national, community and household levels. This study assesses the importance of food storage structures and their utilization by farmers cultivating finger millet (Eleusine coracana) and common beans (Phaseolus vulgaris) in Apac and Arua districts, Northern Uganda. The study encompassed a total sample of 782 households producing finger millet and/or beans (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…This has affected cowpea trade and has severe implications on the economy. Above all, postharvest food losses contribute greatly to food, nutrition, and income insecurity in sub-Saharan Africa (Owach et al, 2017). For this reason, reliable preservative measure(s) need to be sort for.…”
Section: Introductionmentioning
confidence: 99%
“…This has affected cowpea trade and has severe implications on the economy. Above all, postharvest food losses contribute greatly to food, nutrition, and income insecurity in sub-Saharan Africa (Owach et al, 2017). For this reason, reliable preservative measure(s) need to be sort for.…”
Section: Introductionmentioning
confidence: 99%
“…Although relevant factors were identified, the explained variances of such (simple linear) models are very low (e.g. in (Owach et al, 2017) around 20%), indicating that the factors included explain only a small share of differences in adoption rate.…”
Section: Adoption Criteria For Flw Reduction Interventionsmentioning
confidence: 96%
“…Several studies report on the relationship between adoption rate and food loss-related output indicators, applying statistical analyses on farmer characteristics (which could include distance to market) (Adegbola, 2010;Owach et al, 2017). Although relevant factors were identified, the explained variances of such (simple linear) models are very low (e.g.…”
Section: Adoption Criteria For Flw Reduction Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poverty is regarded as the major contributory factor to communities' failure to procure food in SSA (Bain et al, 2013;Ubesie and Ibeziakor, 2013). Without the necessary resources to secure food, many households are deprived from good nutrition due to lack of dietary diversity (Mkonda and He, 2017;Owach et al, 2017). For example, Akombi et al (2017) reported that at least one third of undernourished children in the world reside in Africa, which is mostly comprised of third world countries; thus cementing the fact that poverty leads to PEU.…”
Section: Introductionmentioning
confidence: 99%